Annual review of the sociology of religion. (Annual Review of the Sociology of Religion, 2011)
Over the past thirty years, religion has increasingly played a relevant role, both on a national level and in international affairs. The attempt made by politicians to reframe the policy of social cohesion in a neo-nationalist light (one land, one language, one religion = one political community), demising any kind of multiculturalism, facilitating instead a return to assimilation shaped by fear of the other (culture, religion, language, and so on), is very often associated with a restoration of the primacy of religious discourse in the public sphere. It is not just a return of religion in the public sphere, but the exploitation of religion by politics to reconstruct a social cohesion in the absence of ideological resources.